The Kingstone Bible. Volume 3, Ten commandments - Ayris, Art A.; Pearl, Michael; Ayris, Kelly ([Saint Louis, Missouri] : Kingstone Comics, 2014)
The Kingstone Bible is the most complete graphic adaptation of the Bible ever done. Volume 3 covers God's call to Moses to lead the people out of Israel and into the Promised Land through Joshua leading the Israelites in the conquest of Canaan.
Online resource; title from PDF title page (ebrary, viewed August 31, 2014).
Master record variable field(s) change: 050
Keywords: Ten commandments -- Comic books, strips, etc; Ten commandments; RELIGION -- Christian Theology -- Ethics; Electronic books; Comic books, strips, etc; Comic books, strips, etc